Promoting solidarity in the European Union - Ross, Malcolm (Malcolm G.); Borgmann-Prebil, Yuri. (Oxford : Oxford University Press, 2010)
The EU claims that solidarity is a fundamental value underlying the European social model, yet often stands accused of undermining solidarity by advancing market freedoms. This text provides the first extended study of the idea of solidarity in the EU context from interdisciplinary perspectives - analysing its impact on law and policy.
Description based on print version record.
Includes bibliographical references and index.
Keywords: European Union; European cooperation; European federation; Solidarity -- Political aspects -- Europe; European Union countries -- Politics and government